Developing Digital Literacy Among the Elderly: The Role of Information Technology in Increasing Independence and Skills - Ajeng Kusuma Ningsih; Linda Ratna Fitria Cahyani; Menur Kusumaningtyas (PUTRA JAWA PUBLISHER, 2024)
This research examines the digital literacy of the elderly in Indonesia, focusing on their ability to engage with information technology, particularly in the context of communication and information security. With the rapid development of digital technologies, the elderly face challenges in adopting and utilizing these tools, often due to generational differences, health issues, and a lack of digital education. However, recent studies show an increase in the elderly’s participation in digital platforms, such as WhatsApp, for communication and information access. Despite this, many seniors still struggle with issues like data security, online fraud, and the spread of misinformation. This research emphasizes the importance of improving digital literacy among the elderly to enhance their independence and safety in the digital era. A holistic approach is recommended, including targeted training, community support, and the development of age-friendly digital infrastructure. By increasing awareness and providing adequate resources, the elderly can overcome technological barriers, stay connected, and navigate the digital world more effectively.